Integration of posture and movement: Contributions of Sherrington, Hess, and Bernstein - Stuart, Douglas G. (Human movement science, 2005)
Neural mechanisms that integrate posture with movement are widespread throughout the central nervous system (CNS), and they are recruited in patterns that are both task- and context-dependent. Scientists from several countries who were born in the 19th century provided essential groundwork for these modern-day concepts. Here, the focus is on three of this group with each selected for a somewhat different reason. Charles Sherrington (1857–1952) had innumerable contributions that were certainly needed in the subsequent study of posture and movement: inhibition as an active coordinative mechanism, the functional anatomy of spinal cord-muscle connectivity, and helping set the stage for modern work on the sensorimotor cortex and the corticospinal tract. Sadly, however, by not championing the work of his trainee and collaborator, Thomas Graham Brown (1882–1965), he delayed progress on two key motor control mechanisms: central programming and pattern generation. Walter Hess (1881–1973), a self-taught experimentalist, is now best known for his work on CNS coordination of autonomic (visceral) and emotional behavior. His contributions to posture and movement, however, were also far-reaching: the coordination of eye movements and integration of goal-directed and “framework” (anticipatory set) motor behavior. Nikolai Bernstein (1896–1966), the quintessence of an interdisciplinary, self-taught movement neuroscientist, made far-reaching contributions that were barely recognized by Western workers prior to the 1960s. Today, he is widely praised for showing that the CNS’s hierarchy of control mechanisms for posture and movement is organized hand-in-hand with distributed and parallel processing, with all three subject to evolutionary pressures. He also made important observations, like those of several previous workers, on the goal focus of voluntary movements. The contributions of Sherrington, Hess, and Bernstein are enduring. They prompt thought on the philosophical axioms that appear to have driven their research, and the continual need for emphasis on interdisciplinary, comparative, and transnational approaches to advance movement neuroscience.